224k views
5 votes
Which is the solution of the quadratic equation (4y – 3)2 = 72? y = StartFraction 3 + 6 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction 3 minus 6 StartRoot 2 EndRoot Over 4 EndFraction y = StartFraction 3 + 6 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction negative 3 minus 6 StartRoot 2 EndRoot Over 4 EndFraction y = StartFraction 9 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction negative 3 StartRoot 2 EndRoot Over 4 EndFraction y = StartFraction 9 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction 3 StartRoot 2 EndRoot Over 4 EndFraction

User Rfoo
by
5.8k points

2 Answers

2 votes

Answer:

A

Explanation:

User Xrobau
by
6.1k points
3 votes

Answer:


y = (3 + 6√(2) )/(4) and
y = (3 - 6√(2) )/(4)

y = StartFraction 3 + 6 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction 3 minus 6 StartRoot 2 EndRoot Over 4 EndFraction

Explanation:

The given quadratic equation is (4y - 3)² = 72

We have to solve this equation for y.

Now, 4y - 3 = ± 6√2

⇒ 4y = 3 ± 6√2


y = (3 + 6√(2) )/(4) and
y = (3 - 6√(2) )/(4)

Therefore, the solution is y = StartFraction 3 + 6 StartRoot 2 EndRoot Over 4 EndFraction and y = StartFraction 3 minus 6 StartRoot 2 EndRoot Over 4 EndFraction (Answer)

User Mot
by
5.9k points